eInfoDiscovery@Library Vol. 1/2021: tahukah anda..? (Edisi tentang haiwan) & Dialek Terengganu@PCUiTMCT Bil. 1/2021 / Asmahani Abdullah - Abdullah, Asmahani (Perpustakaan Tun Abdul Razak, 2021)
IQRA': Bil.1/2021 Januari